Synthesis and crystal structure of C2/c Ca(Co, Mg)Si2O6 pyroxenes: effect of the cation substitution on cell volume. (2nd January 2018) - Gori, C.; Tribaudino, M.; Mantovani, L.; Gatta, G. D.; Delmonte, D.; Gilioli, E.; Mezzadri, F.; Calestani, G.
Abstract: A series of clinopyroxenes along the CaMgSi2 O6 –CaCoSi2 O6 join was synthesized by quenching from melts at 1500°C and subsequent annealing at 1250°C (at 0.0001 GPa). This protocol proved to be the most effective to obtain homogenous, impurity-free and stoichiometric pyroxenes. Electron microprobe analyses in energy dispersive mode were conducted and single-crystal X-ray diffraction data were collected on Ca (Co x Mg1- x )Si2 O6 pyroxenes with x = 0.2, 0.4, 0.5, 0.6. Effects of cation substitution at the M 1 site are described. The experimental findings of this study allow us to extend the comparative analysis of the structural features of pyroxenes with divalent cations at the M 1 and M 2 sites.